A Review on the Sustainable Cotton (Gossypium hirsutum) Production - Arshad, Imran (PSM Biological Research, 2020)
Cotton (Gossypium hirsutum) is an important, indeterminate non-food cash crop and a significant source of foreign exchange earnings for Pakistan. The crop generally cultivated over 7 to 8 million acres per year in Pakistan. Pakistan is the fourth-largest producer of cotton in the world and the third-largest exporter of raw cotton. Cotton accounts for 7.3 % of the value-added in agriculture and about 1.6 % in GDP. About 1.3 million farmers cultivate cotton over 3 million hectares, covering 15% of the cultivable area in the country. The overall average per acre yield of Cotton in Pakistan is very low as compared to the other countries i.e. China, USA, India, Brazil, Turkey, Egypt, and Iran. From the past few years in Pakistan due to BT cotton variety, some of our farmers are taking handsome yield. This paper describes an idea to the readers how they can increase the yield of cotton by managing the critical stages of cotton production on time to obtain a bumper crop.